Digital Financial Governance Transformation in Urban Food Supply SMEs - Iswari, Hanif Rani; Laili, Choirun Nisful; Vemy Martha Aulia; Jedina, Aurelia (Badan Perencanaan Pembangunan Kota Malang, 2026)
This study examines how digital financial governance transformation reshapes informal financial recording practices and strengthens governance quality within urban food supply SMEs in Malang City. Existing studies on SME digitalization predominantly emphasize technological adoption and operational efficiency, while limited attention has been given to the behavioral and organizational mechanisms through which governance transformation becomes embedded within daily operational systems. Addressing this gap, the study adopts a case-based quasi-experimental design integrating a stepped-wedge implementation strategy with interrupted time series (ITS) analysis across three embedded outlets of Omah Sayur MQS, an urban food supply SME operating within Malang City’s local food distribution network. The intervention was implemented sequentially through standardized financial recording procedures, adoption of real-time digital recording systems, and continuous monitoring designed to support behavioral adaptation and procedural compliance. Data were collected longitudinally through structured observation, in-depth interviews, and financial document analysis covering pre-intervention, transition, and post-intervention phases. The findings reveal that baseline financial practices were characterized by delayed reporting, fragmented documentation, retrospective recording routines, and weak procedural standardization. Following intervention exposure, substantial improvements emerged in recording accuracy, reporting timeliness, documentation consistency, and managerial visibility. Interrupted time series patterns demonstrate both immediate level changes and sustained trend stabilization, indicating that governance transformation evolved progressively through behavioral internalization and routinized compliance across outlets. Beyond firm-level operational improvement, the findings show that governance standardization strengthened coordination, transparency, and information reliability across organizational units, thereby supporting broader urban SME ecosystem governance. The study further demonstrates that financial governance quality contributes to the reliability and coordination of urban food supply systems, particularly in relation to policy-oriented distribution initiatives such as the Free Nutritious Meal (MBG) program. This study proposes a Financial Governance Transformation Model for Urban Food Supply SMEs that conceptualizes digital governance transformation as a multi-level process operating across firm, ecosystem, and policy system dimensions. The study contributes to the literature by repositioning SME digitalization as a longitudinal governance restructuring process shaped by behavioral adaptation, organizational internalization, and ecosystem coordination rather than merely technological adoption.